THE MOLECULAR DETECTION OF CITRUS VEIN PHLOEM DEGENERATION (CVPD) PATHOGEN (Liberobacter asiaticus) IN Diaphorina citri KUWAYAMA (HOMOPTERA : PSYLLIDAE) AND OTHER INSECTS ASSOCIATED WITH CITRUS PLANT - I Nyoman Wijaya; Wayan Adiartayasa; Made Sritamin (International Journal of Biosciences and Biotechnology, 2018)
The research was coducted at Laboratory of Biotechnology Faculty of Agriculture Udayana University. The purpose of this research were to investigate moleculer detection of CVPD pathogen in its vector, other phytophagous insects on citrus cv, Siam and kemuning (Murraya paniculata L. Jack.). The result of this research showed that adults and nymphs of Diaphorina citri Kuw. could transmit CVPD disease, but the pathogen of CVPD could not be transovarially transmited. As a host of CVPD disease , kemuning could be source of infection. The adult of Toxoptera citricidus Kirkaldy and Maleuterpes dentipes Hell. could not potensial transmited CVPD disease.